Assessing crop water stress of winter wheat by thermography under different irrigation regimes in North China Plain - Zia, Shamaila; Du, Wenyong; Spreer, Wolfram; Spohrer, Klaus; He, Xiongkui; Muller, Joachim (International Journal of Agricultural and Biological Engineering, 2012)
Thermal imaging can be used as an indicator of water stress due to the closure of stomatal aperture. In this paper, we analyzed the robustness and sensitivity of thermography of winter wheat in the North China Plain. The seasonal and diurnal variations of Crop Water Stress Index (CWSI) were evaluated. Five treatments were applied by means of irrigation, with plots receiving 100% of ETo(DI), 50%(D50), 16%(D16) and no irrigation(NI). A high correlation was found between stomatal conductance (gs) and CWSI, depending on the phenological stage of the crop with R2 = 0.44 at pre-heading stage and R2 = 0.77 at post-heading stage. In addition, a high correlation between yield and CWSI at different growth stages indicates that thermography can predict yield. Hourly measurements of canopy temperature were taken to study the effect of the time of day on image acquisition and it was found that midday was the most appropriate time. These results should assist in designing precision irrigation scheduling for setting the threshold values.Keywords: CWSI, Triticum aestivum L., stomatal conductance, canopy temperature, yieldDOI: 10.3965/j.ijabe.20120503.003Citation: Zia S, Du W Y, Spreer W, Spohrer K, He X K, M